How to Implement an Accurate and Effective Costing System in Manufacturing Organizations - Boris Popesko (European Financial and Accounting Journal, 2009)
The objective of the article is to define rules for establishing a high quality costing system to measure the costs of products, customers, and other cost objects in a manufacturing enterprise. The pros and cons of all existing costing methods are discussed in the article, as are the methods themselves. Furthermore, their allocation principles are investigated, along with the nature of costs and the behavior of cost elements in major enterprises. One expectation is that different principles of cost allocation will have to be applied to different types of costs, based on their relation to the output of a company's processes. Initially, several analyses are performed in order to identify the methods that prove insufficient for effective and accurate cost allocation. These methods, despite their inaccuracies, are very frequently used in practice. Also, cost elements or cost pools inside an organization, which tend to be hard to allocate accurately, are identified. Secondly, several implementation projects on the activity-based costing system, have been analyzed in order to consider the effectiveness of utilizing such a system in a manufacturing enterprise. Furthermore, the general rules for allocating cost pools or activity costs are outlined. Thirdly, different principles for cost allocation are defined for individual cost elements. The result of the article is to define the rules for implementing a costing system which provides accurate and correct information. These rules should provide for a compromise between the use of a traditional absorption costing system and the activity-based costing system, by pointing out the most important allocation principles.
Keywords: M1; M41; 650; Costing Methods; Cost Allocation; Activity-based Costing